Fumaric acid esters: a new therapeutic option for skin manifestations in lupus erythematosus?. (February 2017) - Kuhn, A.; Landmann, A.; Bonsmann, G.
Abstract : Linked Article:Saracino and Orteu Br J Dermatol 2017; 176:472–480 .